Deteksi Dini dan Pencegahan Kerusakan Ginjal Melalui Pemeriksaan Tekanan Darah dan Glukosa Darah Secara Rutin Pada Kader Kesehatan Purwokerto - Sumeru, Annas; Sari, Yunita; Anam, Akhyarul (Jurnal of Community Health Development, 2021)
Kidney disease is a disease that is feared by many people because the kidneys fail to function to remove metabolic waste. There are 15 health cadres in Sokanegara sub-district, some of which are new cadres who are being trained to replace the old cadres. Through this science and technology application program, it is hoped that health cadres will gain knowledge and skills about early detection and efforts to prevent kidney failure. This science and technology application program is carried out through needs-based health education through extension methods, discussions, and demonstrations on preventing kidney damage. Extension activities increase the knowledge of health posyandu cadres, the knowledge score is measured before and after the provision of education, the average pre-test score for the knowledge of health cadres obtained is 63.3, while the average post-test score for the knowledge of health cadres is 82. The results of the paired t test analysis showed that the value (p = 0.00). The results of the analysis indicate that there is a significant relationship or difference between the scores of knowledge scores of health cadres in Sokanegara sub-district, East Purwokerto sub-district on the understanding of early detection and prevention of kidney failure before and after education. The PKM program for implementing science and technology has been running smoothly and has produced services in the form of providing counseling by experts in the health sector on early detection and prevention of kidney failure, modules, and published texts.